2016
DOI: 10.1007/s12032-016-0795-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and clinical evaluation of a novel lozenge containing polaprezinc, a zinc-L-carnosine, for prevention of oral mucositis in patients with hematological cancer who received high-dose chemotherapy

Abstract: We previously reported that oral ingestion of polaprezinc, a zinc-L-carnosine, suspended in sodium alginate solution prevents oral mucositis in patients receiving radiotherapy or high-dose chemotherapy. In the present study, we developed a novel preparation of polaprezinc and evaluated clinical effect of the lozenge preparation in patients receiving high-dose chemotherapy for hematopoietic stem cell transplantation. The preparation contained 18.75 mg polaprezinc in a tablet and showed an excellent uniformity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 30 publications
1
41
1
7
Order By: Relevance
“…The polaprezinc lozenge can be easily taken; thus, it is suitable for outpatients and hospitalized patients. [34] The prevention management of mucositis is summarized in Table 1.…”
Section: Oral Mucositismentioning
confidence: 99%
“…The polaprezinc lozenge can be easily taken; thus, it is suitable for outpatients and hospitalized patients. [34] The prevention management of mucositis is summarized in Table 1.…”
Section: Oral Mucositismentioning
confidence: 99%
“…8 Various treatments for managing oral mucositis (eg, amifostine, benzydamine, and palifermin) have been proposed and tested. [9][10][11][12][13] However, most of the current interventions are only palliative and predominantly focused on improving oral hygiene and providing symptom control. 9,[12][13][14] Thus, the development of more effective treatment options for oral mucositis is highly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for recently published articles about zinc, a RCT reported that zinc sulfate reduced the incidence and severity of OM in leukemia patients undergoing CT [81]. Additionally, zinc was reported to be effective in 2 comparative studies; one conducted in HSCT and the second conducted in RT for H&N cancer [12,82].…”
Section: Discussionmentioning
confidence: 99%